PENINGKATAN KEMAMPUAN MEMBACA PEMAHAMAN SISWA KELAS IV SDN 002 PASIR SIALANG MELALUI PENERAPAN MODEL PEMBELAJARAN SURVEY, QUESTION, READ, RECITE, REVIEW (SQ3R) - Alta Feros; Nurmalina; Ramdhan Witarsa; Musnar Indra Daulay; Molli Wahyuni (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Reading comprehension is an essential skill in learning Indonesian language. However, many students still struggle to fully understand the content of texts. This study aims to improve the reading comprehension skills of fourth-grade students at SDN 002 Pasir Sialang through the application of the SQ3R model (Survey, Question, Read, Recite, Review). This research employs a Classroom Action Research (CAR) method conducted in two cycles, each consisting of planning, action, observation, and reflection stages. Data collection techniques include tests and non-test instruments, while data analysis uses descriptive quantitative and qualitative approaches. The results show an improvement in students’ reading comprehension, with classical completeness increasing from 62% in the first cycle to 84% in the second cycle. Students became more active, confident, and better able to comprehend reading materials. Based on these findings, the SQ3R model is effective in enhancing reading comprehension for fourth-grade students. This study recommends the use of the SQ3R model as an engaging and meaningful learning strategy.